Interpretação: questão na clínica de linguagem com crianças - Santos, Brenda de Sousa (2021)
This dissertation develops a theoretical discussion on Interpretation in the clinic with children. To this end, it returns, initially, to publications in Interactionism and in the Language Clinic, in the search for the path taken in these fields on the effects of the interpretation of the other on children's speeches. Based on the complexification of the relationship between “speech” and “listening”, which gains greater prominence in Andrade's thesis (2003), this dissertation intends to illuminate the interpretation as an effect of the significant movements in symptomatic speeches on the clinician's listening, which is only possible to indicate due to the implication of the structural functioning of language as a third part in the child-other relationship - inheritance of European Structuralism and Interactionism for the Language Clinic. New steps in the discussion are suggested here based on the dialogue with Freud (1900 and 1937), which makes one think and moves the reflection in the direction of assuming the interpretation as produced about “fragments” of speech, in the tension between “disassembly” and “assemblies” of strange statements. The therapist's interpretation of the child's speech is approached, therefore, as an effect of listening to the functioning of the language and takes place as an “act”, which involves the return to the clinical history between the child and the therapist. “Listening” and “interpretation”, here, are not confused, but they are inseparable. These elaborations open the way for future studies on the “act” at the Language Clinic, especially in addressing cases on which there is more of a “speaking body” than sound speech materiality